(untitled) (World Science, 2020)
The article reveals relevance and practical need for the formation of preschool and primary education of health care competence in future teachers. Analysed statistical data from the Ministry of Health regarding health status of children aged 0-17; a steady tendency was found for an increase in the number of children with diseases of different genesis. The experience of work of the Khortytsia National Academy of Pedagogy on the formation of preschool and primary education of health-saving competence in future teachers is presented. On the basis of generalisation of theoretical and methodological principles of professional training in future teachers of preschool and elementary education institutions, a practical-oriented approach to the system formation of health-saving competence is created by creating in the college a health-friendly environment.